Adherence to dietary recommendations and colorectal cancer risk: results from two prospective cohort studies. (15th June 2019) - Nguyen, Sang; Li, Honglan; Yu, Danxia; Gao, Jing; Gao, Yutang; Tran, Huong; Xiang, Yong-Bing; Zheng, Wei; Shu, Xiao-Ou
Abstract: Background: Understanding the association between diet and colorectal cancer (CRC) risk is essential to curbing the epidemic of this cancer. This study prospectively evaluated adherence to the Chinese Food Pagoda (CHFP), and two American Dietary Guidelines: the Alternative Healthy Eating Index (AHEI-2010) and the Dietary Approaches to Stop Hypertension (DASH) in association with CRC risk among Chinese adults living in urban Shanghai, China. Methods: Participants included 60 161 men and 72 445 women aged 40–74, from two ongoing population-based prospective cohort studies. Associations between dietary guideline compliance scores and CRC risk were evaluated by Cox proportional hazard regression analyses, with age as time metric, and potential confounders were adjusted. Results: We identified 1670 CRC incidence cases (691 males and 979 females) during an average 8.1 years of follow-up for men and 13.4 years for women. CHFP score was inversely associated with risk of CRC, with hazard ratios (HRs) (95% confidence intervals) of 0.88 (0.77, 1.00), 0.86 (0.75, 0.98) and 0.84 (0.73, 0.96) for the 2nd, 3rd and 4th quartiles versus 1st quartile, respectively ( Ptrend = 0.01). The inverse association appeared stronger for rectal cancer, individuals at younger age (< 50 years), with a lower BMI (<25 kg/m 2 ) or without any metabolic conditions at baseline, although no multiplicative interactions were noted. No consistent association pattern was observed for the modified DASH score and the modified AHEI-2010. Conclusions: Compliance with the Dietary Guidelines for Chinese was associated with reduced risk of CRC among Chinese adults. To maximize health impacts, dietary recommendations need to be tailored for specific populations.